If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -9x = 5x + -10x + -2 Reorder the terms: 6 + -9x = -2 + 5x + -10x Combine like terms: 5x + -10x = -5x 6 + -9x = -2 + -5x Solving 6 + -9x = -2 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 6 + -9x + 5x = -2 + -5x + 5x Combine like terms: -9x + 5x = -4x 6 + -4x = -2 + -5x + 5x Combine like terms: -5x + 5x = 0 6 + -4x = -2 + 0 6 + -4x = -2 Add '-6' to each side of the equation. 6 + -6 + -4x = -2 + -6 Combine like terms: 6 + -6 = 0 0 + -4x = -2 + -6 -4x = -2 + -6 Combine like terms: -2 + -6 = -8 -4x = -8 Divide each side by '-4'. x = 2 Simplifying x = 2
| 12f+7=100 | | [6-(2-6(2-4)+5)]+4= | | 12+(12-x)=80 | | 3x-4-6(x+4)=0 | | (X+2)(X)=144 | | -22+(-7)= | | 18x^3+48x^2-12x^2=0 | | X=32500-23280 | | 16(n-2)-(n+3)=10 | | f(6)=7x-15 | | 9x^2+6x-10=0 | | 20s+6=5 | | 3(4x-9)=5(3x-5) | | 32x^2-162=0 | | 11+6x-15-4x=2 | | -2.5-32.7=74.1 | | y=ln(4x-8) | | -12=-2k+-4k | | 2x^2+7=-23 | | -12=-2 | | 5x+55=2x+100 | | 6y+4=2x-1 | | y=-5x^2+20t+0.8 | | 7+13= | | 12x+7=8x+15 | | 3(9+7d)=-16 | | 1-cosx-cosx+cos^2x= | | 3(4x+6)=-37+19 | | -30r=-5r+6r | | =(5x^2y^3)(-x^5y)(-2x^4y) | | 10x+7=3x+21 | | 12x-11y=88 |